Impaired Colour Vision and Contrast Sensitivity in Patients with Diabetes Mellitus - Amna Yasmeen, Rida Ahmed, Anila Naz, Muhammad Yasir Malik, Hira Tariq (Pakistan Journal of Ophthalmology, 2018)
Purpose: Diabetes mellitus distresses the physiology of the retinal neurons which causes diabetic retinopathy with impaired vision, colour vision defect and contrast sensitivity and these are the common causes of legal visual loss in diabetes mellitus. This study determines the major factors which lead to the complications in diabetic patients irrespective of diabetes status. Study Design: Cross-sectional study. Place and Duration of the Study: Department of Ophthalmology, Dow University Hospital. Methods: A total of two hundred patients were included. Information regarding types of diabetes (T1DM/T2DM), diabetic status (controlled/uncontrolled), Snellen acuity, and color vision and contrast sensitivity was collected from eye OPD along with demographic of patients. Result: Mean age of the patients was 50.23 ? 7.89 years. There were 51% males and 49% females. Majority of the patients were married 87%. 60.5% had controlled diabetes while 39.5% uncontrolled diabetes was observed in patients (T2DM 76.5%; T1DM: 23.5%). Snellen visual acuity of right eye (27%) and left eye (28%) found more in patients with 6/9. Status of diabetes was found significantly associated with colour vision deficiency (p-value 0.031). Diabetic patients, who were using glasses, were 2.2 folds more susceptible to have defects in contrast visual acuity than those who were not using glasses (ORadj=2.2, 95% CI: 1.0 ? 4.7). Conclusion: The findings of our study showed that colour vision deficiency was found significantly associated with diabetes status (controlled/uncontrolled) while contrast vision was significantly associated with those who were using glasses. Keywords: Diabetic retinopathy; Snellen chart; colour vision; contrast sensitivity; diabetes mellitus.